Thermochemical liquefaction of pinewood shaves – Evaluating the performance of cleaner and sustainable alternative solvents. (1st July 2021) - Amado, Mariana; Bastos, David; Gaspar, Daniela; Matos, Sandro; Vieira, Salomé; Bordado, João Moura; Galhano dos Santos, Rui
Abstract: Thermochemical liquefaction can convert lignocellulosic biomass into a chemical platform for alternative biofuels or chemical synthons. The process is conducted with a solvent and an acidic catalyst at mild temperatures and atmospheric pressure. Most solvents used to conduct the process are petroleum-based. Studies involving more sustainable solvents are needed so that the global process can also be more sustainable and cleaner. The surplus of glycerol (e.g., biodiesel production), once derived from a vegetable source, can be converted into renewable and sustainable solvents, thus turning the liquefaction process cleaner. Pinewood shaves were liquefied with 2-ethylhexanol, set as a reference solvent, resulting in a biomass conversion of 71.2%. The liquefaction with the different solvents was carried out under the same conditions using pure solvents or combined with 2-ethylhexanol. The process with cyclic carbonates, from propylene and glycerol, led to the highest conversions, 96.5% and 98.7%, respectively. Additionally, the use of two glycerol acetals, solketal and formal glycerol, afforded bio-oils with high conversion rates, as well (>95%). On the other hand, the liquefaction of the biomass with propylene glycol converted to 79.4%. The bio-oils obtained from pinewood shaves' liquefaction with glycerol carbonate and propylene carbonate led to significantly better calorific properties than those from the biomass itself. Graphical abstract: Image 1 Highlights: Pinewood shave was submitted to thermochemical liquefaction. Novel sustainable, cleaner and bio-based solvents were used as liquefaction solvent. Pinewood shaves liquefaction improvement by the use of cyclic carbonates. The use of glycerol carbonate as a liquefaction solvent led to a conversion of 98.7%.